Exchange rate fundamentals and order flow - Evans, Martin D. D. 1960-; Lyons, Richard K. 1961- (Working paper series / National Bureau of Economic Research, 2007)
We address whether transaction flows in foreign exchange markets convey fundamental information. Our GE model includes fundamental information that first manifests at the micro level and is not symmetrically observed by all agents. This produces foreign exchange transactions that play a central role in information aggregation, providing testable links between transaction flows, exchange rates, and future fundamentals. We test these links using data on all end-user currency trades received at Citibank over 6.5 years, a sample sufficiently long to analyze real-time forecasts at the quarterly horizon. The predictions are borne out in four empirical findings that define this paper's main contribution: (1) transaction flows forecast future macro variables such as output growth, money growth, and inflation, (2) transaction flows forecast these macro variables significantly better than the exchange rate does, (3) transaction flows (proprietary) forecast future exchange rates, and (4) the forecasted part of fundamentals is better at explaining exchange rates than standard measured fundamentals.